THU0038 Histologic features of osteochondral junction in joint disorders. (23rd January 2014) - Addimanda, O.; Pavloska, B.; Pulsatelli, L.; Lisignoli, G.; Facchini, A.; Meliconi, R.
Abstract : Background: Osteochondral junction (OCJ) is a crucial region in OA onset and progression. Characteristic feature of OCJ are: calcified cartilage, tidemark and possible vascular invasion. New blood vessels from the subchondral bone may invade calcified cartilage and even breach the tidemark. (1). Objectives: To investigate the histologic features of cartilage and OCJ in Osteoarthritis (OA), Inflammatory Arhritis (IA) and Post-Traumatic Cases (PTC). Methods: Osteochondral biopsies were obtained from the surgical specimens of 60 patients with OA, 11 patients with IA and 23 PTC who underwent joint replacement (knee, hip, shoulder) because of arthritis or traumatic fractures. Biopsies (3 samples per patient) were processed as previously described (2) and paraffin embedded. 5 μm slides were cut and stained with Ematossilin-Eosin and with Safranin-O and evaluated utilizing Mankin and Chambers scores, in order to quantify cartilage damage. Tidemark duplication and cartilage-subchondral vascular invasion (numbers of vessels crossing osteochondral junctions) were evaluated. Demographic features (sex, age and BMI) from all patients were recorded. Results: Arthritis patients were older and with a slightly higher BMI than PTC [age (mean ± sd) =73.6±7.2 vs 71.9±12.0, p=0.04; BMI (mean ± sd) =29.5±4.1 vs 28.8±4.6, p=0.02]. We found a significantly higher total Mankin score in OA and IA patients compared to PTC [Total Mankin score OA + IA (mean ± sd) =7.24±2.96 vs PTC 4.120±3.25, p = <0.0005] without significant differences between OA and IA cases [OA Total Mankin score (mean ± sd) =6.58±3.01 vs IA Total Mankin score (mean ± sd) 7.90±2.92, p=0.89]. Same results were obtained utilysing Chambers scores. Tidemark duplication was found in similar percentages in all three groups (OA =52%, RA =44%, PTC =33%, p=0.61 – Kruskall-Wallis test). The number of OCJ invading vessels was higher in arthritis (OA and IA) samples compared to PTC ones (p=0.0079).A correlation between Mankin score and the number of vessels invading calcified cartilage was found only in IA patients (p=0.0008), but not in OA and PTC samples. Conclusions: Cartilage damage, vessel OCJ invasion and tidemark duplication is similar in OA and IA. Therefore our study questions the OA specificity of tidemark duplication and vascular invasion of calcified cartilage. References: Fransès R.E, McWilliams D.F, Mapp P.I, Walsh D.A. Osteochondral angiogenesis and increased protease inhibitor expression in OA. Osteoarthritis and Cartilage 2010;18:563–571. Lisignoli G, Toneguzzi S, Grassi F, Piacentini A, Tschon M, Cristino S, Gualtieri G, Facchini A. Different chemokines are espresse in human arthritic bone biopsies: IFN-gamma and IL-6 differently modulate IL-8, MCP-1 and rantes production by arthritic osteoblasts. Cytokine 2002;20:231-8. Disclosure of Interest: None Declared